2010
DOI: 10.1143/jjap.49.04da17
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable NiSi Gate Electrode with TiN Barrier Metal for High-Density NAND Flash Memory Devices

Abstract: We report the large-scale assembly of type-switchable field effect transistors (FETs) based on carbon nanotubes (CNTs) and nanoparticles (NPs). In this device, the charges stored in NPs adjacent to ambipolar CNT channels were adjusted to control the carrier type and density in the channels. We demonstrated the real-time reconfiguration of individual FET types and logic circuit functionality. Theoretical simulation of a model system was provided to explain this doping effect. This work takes advantage of the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…11,12) The atomic layer deposition (ALD) method has attracted increasing attention to accomplish an ultrathin and conformally deposited film without defects. [13][14][15][16][17][18][19] Among several diffusion barrier materials, such as TaN, TiN, and WN, WN is considered to be a promising DBL material in terms of resistivity, growth temperature, and melting point. 20) However, it has been reported that the precursor WF 6 for the deposition of the WN layer has some critical issues: substrate encroachment, volcano formation, and thickness variations on different substrates.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) The atomic layer deposition (ALD) method has attracted increasing attention to accomplish an ultrathin and conformally deposited film without defects. [13][14][15][16][17][18][19] Among several diffusion barrier materials, such as TaN, TiN, and WN, WN is considered to be a promising DBL material in terms of resistivity, growth temperature, and melting point. 20) However, it has been reported that the precursor WF 6 for the deposition of the WN layer has some critical issues: substrate encroachment, volcano formation, and thickness variations on different substrates.…”
Section: Introductionmentioning
confidence: 99%